French Modality of Verb Modal in Directive Acts on Michel Vaillant's Comic - Yuliantini - Yuliantini (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
Each language has a modality to express the speaker's attitude. The form that describes the attitude of the speaker is in the form of grammatical elements and there are also lexical elements. In French, the lexical attitude of the speaker can be characterized by capital verbs such as vouloir, devoir, pouvoir and falloir. This paper discusses the modalities in directive speech acts in its use in French in French-language comics namely Michel Vaillante. This article aims to find out the function of using modal modal verb modalities realized by Michel Vaillante comics. Data is collected from Michel Vaillante comics downloaded from the online version of the Culturethèque website. Data collection was done using the 'see' method, then analyzed using the agih method with the basic technique 'for direct elements'. The last step is the method of presenting data. The author uses formal and informal methods in presenting the results of data analysis. The results show that the function of the French modal modal verb in directive speech acts expresses the meaning of governing, suggesting, and expressing hope. The capital verbs used are devoir, pouvoir, vouloir, and falloir.Keywords: modalities, French, capital verbs, directive speech acts.